Numeracy-Based Teaching Material with Data Presentation Topic to Support Students' Numeracy Skills - Gresilia Situmorang; Hapizah Hapizah; Budi Mulyono; Ely Susanti (Kreano: Jurnal Matematika Kreatif-Inovatif, 2023)
Numeracy is the ability to identify, describe and communicate various types of numbers and mathematical symbols to solve mathematical tables, graphs, and problems. There are few math teaching materials, especially those based on numeracy. The research aims to produce numeracy-based teaching material that is valid, practical and potentially supports numeracy skills. The following type of research is development. The research subjects were students of class VII at Senior high school in Pagar Aam. The stages of the research consisted of preliminary study and formative evaluation (Expert Review, One to One, Small Group and field tests) with the instruments used, namely questionnaires, tests, and interviews. This study states that the teaching material used can help improve numeracy skills, and the developed teaching material is declared valid without revision. This shows that with the help of numeracy-based teaching, the material can help students improve their numeracy skills in understanding data presentation material. Mathematics teachers can further use these numeracy-based teaching materials to improve students’ numeracy skills.